Novel Biocomposite Engineering and Bio-Applications - Gary Chinga Carrasco (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The engineering and utilization of biocomposites is a research field of major scientific and industrial interest worldwide. The biocomposite area is extensive and spans from structured and solid biocomposites (e.g., reinforced bioabsorbable polymers), films (e.g., antimicrobial barriers), to soft biocomposites (e.g., use of alginates, collagen and nanocellulose as components in bioinks for 3D bioprinting). Key aspects in this respect are the appropriate engineering and production of biomaterials, nanofibres, bioplastics, their functionalization enabling intelligent and active materials, processes for effective manufacturing of biocomposites and the corresponding characterization for understanding their properties. The current Special Issue emphasizes the bio-technological engineering of novel biomaterials and biocomposites, considering also important safety aspects in the production and use of bio- and nanomaterials.